Perspectives Regarding Culturally Responsive Teaching in a Mixed-Gender Online Learning Community - Nouf Alsuwaida (SAGE Open)
This study investigated the experiences of learners in an online mixed-gender classroom to understand how distance education has changed society in Saudi Arabia. The study integrated culturally responsive teaching (CRT) as a theory of instruction with gender-responsive digital pedagogy through an online course. This study highlights how distance learning encourages gender equality in teaching and learning through a digital arts online course. It employed a quasi-experimental method, which included per-survey, questionnaires, and observation. The sample comprised 87 male and female participants who attended an online course at an institution in Saudi Arabia in 2024. The results showed that learners’ perspectives of the Digital Arts online course demonstrated strong agreement, primarily focused on the positive aspects of online learning. Learners overwhelmingly supported the online course and its cost-effectiveness, collaborative nature, skill development, accessibility, and contribution to equality, job opportunities, and cultural exchange. Furthermore, the thematic analysis identified four themes: (1) development of the curriculum and instruction using CRT in distance education; (2) enhancing learning outcomes by building various technology-based activities to break gender segregation; (3) building caring, respectful, and cooperative relationships in a mixed-gender learning environment; and (4) Saudi society and cultural transformation to empower learners in a mixed-gender learning environment. The study provided positive results for collaborative learning among students of different genders. It also highlights important information on how technology can change Saudi culture and society and segregate gender.